The Banking Sector in Sudan: Between New Opportunities and Challenges - ANIL DHASMANA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In recent years, the development of information technology has had a great impact on almost all areas of life. Electronic banking services have enabled the banking industry to benefit from this. E-banking is the trend of the future as it has several advantages that give banks a competitive edge over their competitors and increase consumer satisfaction through better service. A number of factors may still hinder the success of online banking services, which are a major problem for consumers and financial institutions. The purpose of this essay is to review and focus on the many benefits and services offered by e-banking in the Sudanese banking sector and the associated difficulties. Despite the many electronic banking services available in Sudan, there are many obstacles to their successful implementation. This paper used an analytical/qualitative approach to analyse this issue. Excel was used to evaluate the primary and secondary data obtained.